Comprehensive assessment of the varietal fund of quince (Cydonia oblonga Mill.) in the conditions of Krasnodar region - T. G. Prichko; L. D. Chalaya; N. V. Mozhar (Вавиловский журнал генетики и селекции)
Introduction to industrial horticulture varieties of quince, characterized by winter hardiness, high productivity and good product qualities and valuable chemical composition, is one of the priorities in breeding. The article presents a selection of parental pairs, taking into account their biologically and economically valuable traits: Ispolinskaya (yield of large fruits); Cаunchi 8 (fruit quality); Zolotistaya and Muskatnaya (yield, high winter hardiness and drought resistance); and Kubanskaya (tree growth restraint). Varieties with horizontal resistance to monilia are Muskatnaya, Novogodnyaya, Urozaijnaya kubanskaya and Sophia. The timing of flowering was determined for early-flowering Dyuna and Nivushka and late-flowering Aurora, Novogodnyaya and Rumo. Aurora, Zoloto skifov, Podarochnaya, Urozaijnaya kubanskaya and Sophia were identified as high-yield varieties, with maximum environmental adaptation to adverse environmental factors. Based on hybridological analysis, the inherited traits that characterize their commercial quality (apple-shaped fruits and fruit size) have been identified; the varieties with the most stable technical performance (the coefficient of variation V = 8.5–10.0 %) are Novogodnyaya, Nivushka and Podarochnaya. Varietal differences in the content of vitamins and polyphenols have been identified between new varieties and cultivars taken for crossing: Zolotistaya (28.4 mg/100 g), Novogodnyaya (33.3 mg/100 g) and Podarochnaya (32.3 mg/100 g) are high in vitamin C; Kubanochka (225.0 mg/100 g), Novogodnyaya (222.2 mg/100 g) and Podarochnaya (196.8 mg/100 g) are high in P-active catechins, which allows you to replenish your assortment of quince for the South of Russia with valuable genotypes of quince (Cydonia oblonga Mill.) competitive varieties of selection by the North-Caucasus Zonal Scientific-Research Institute of Horticulture and Viticulture.